Pengaruh Resiko Pembiayaan Dan Resiko Likuidalitas Terhadap Profitabilitas Bank Syariah - Rahma Sonang Ritonga; Ratih Mala; Siti Tri Adha; Hasyim Hasyim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to investigate the influence of liquidity risk on the profitability of Sharia Banks. Liquidity risk is an important factor that can influence a bank's financial performance, especially in the context of Sharia banks that operate specific sharia principles. The research method used is a quantitative approach using financial data from registered Sharia banks. The data collected covers the last five year period. The research variables studied are liquidity risk and bank profitability. The research results show that high liquidity risk can have a negative impact on profitability which can disrupt bank operations and reduce income. Effective liquidity risk management is key to minimizing this negative impact. Sharia banks need to adopt appropriate strategies and policies to manage liquidity risk well, including careful supervision of cash flows, diversification of funding sources, and development of investment instruments that comply with sharia principles. By managing liquidity risk well, banks can minimize its negative impact on profitability.